Diversity of science linkages: A survey of innovation performance effects and some evidence from Flemish firms - Bruno Cassiman; Reinhilde Veugelers; Pluvia Zuniga (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
This paper discusses the diversity of mechanisms which firms can deploy to link to science and how science links are associated with their innovation performance. Using a sample of Flemish firms, we show that there exists considerable heterogeneity in the type of links to science at the firm level. Overall, firms with a science link enjoy superior innovation performance, in particular with respect to innovations that are new to the market. At the invention level, our findings confirm that patents from firms engaged in science are more frequently cited and have a broader technological and geographical impact. We show that it is crucial to distinguish between direct science links at the invention level and indirect science links at the firm level to encounter distinct positive effects.
Keywords: O32; O34; L13; 330; Innovation; cooperation; patents; forward citation; science; industrial innovation; Forschungskooperation; Innovation; Unternehmensentwicklung; Industrielle Forschung; Erfindung; Patent; Belgien